Do energy-pollution-resource-transport taxes yield double dividend for Nordic economies? - Alola, Andrew Adewale; Nwulu, Nnamdi (Elsevier, 2022)
With the policy performance of the Nordic countries especially from the aspects of energy security, energy equity, and environmental sustainability, this study provides more in-depth on the performance of the countries’ disaggregated environmental taxes. To examine the greenhouse gas emission and energy intensity effects of energy tax, pollution tax, resource tax, and transport tax alongside controlling for the role of employment rate and gross domestic product over the period 1995–2020, empirical tools such as the method of moments quantile regression, short- and long-run cointegration, and Granger causality approaches were utilized. Importantly, there are series of interesting results from this investigation. Firstly, the result posits the feasibility of Green growth in the panel of Nordic countries while a significant and negative nexus between GDP and energy intensity was also established. Secondly, also from the panel result, we found that only energy tax significantly mitigates both emissions and energy intensity across the quantiles while pollution tax and resource tax exacerbate emissions and energy intensity. Thus, for the panel case, only energy tax could validate the double dividend hypothesis. Thirdly, the result revealed that double dividend hypothesis and by large extent co-benefit is achievable with pollution and resource tax policies in Finland but in the short-run. Similarly, pollution, resource, and transport tax policies in Sweden are all desirable for achieving both environmental and economic benefits in the short-run. However, there is no valid evidence to support the validity of double dividend hypothesis in Denmark and Norway. Lastly, we found a one-way Granger causality from GDP, energy tax, resource tax, and transport tax to greenhouse gas emission while a one-way Granger causality also exists from GDP, energy tax, and transport tax to energy intensity. Overall, compelling policy dimensions are inferred from the investigation.
Keywords: Co-benefit; economic growth; employment; Environmental-related taxes; Nordic countries; fi=Taloustiede|en=Economics|